2021
DOI: 10.3390/ijms22020577
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Mesoporous Mg- and Sr-Doped Nanoparticles for Moxifloxacin Drug Delivery in Promising Tissue Engineering Applications

Abstract: Mesoporous silica-based nanoparticles (MSNs) are considered promising drug carriers because of their ordered pore structure, which permits high drug loading and release capacity. The dissolution of Si and Ca from MSNs can trigger osteogenic differentiation of stem cells towards extracellular matrix calcification, while Mg and Sr constitute key elements of bone biology and metabolism. The aim of this study was the synthesis and characterization of sol–gel-derived MSNs co-doped with Ca, Mg and Sr. Their physico-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 99 publications
(85 reference statements)
1
46
0
Order By: Relevance
“…The incorporation of Ca led to stronger network connectivity compared to Si-NP, indicated by the decrease in the shoulder around 960 cm −1 , while the addition of Ce led to a further reduction in the shoulder. Thus, it is concluded that Ca and Ce behave as network modifiers [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The incorporation of Ca led to stronger network connectivity compared to Si-NP, indicated by the decrease in the shoulder around 960 cm −1 , while the addition of Ce led to a further reduction in the shoulder. Thus, it is concluded that Ca and Ce behave as network modifiers [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Highly bioactive glasses are able to elicit a biological response at their surface that leads to the formation of a bond with the tissues when they are soaked in human plasma [ 61 ]. As mentioned before, there is a relation between the percentage and kind of Si–O–NBO of the pristine material and the formation of silica-gel and Ca-P layers [ 31 ]. Bioactive glasses containing a high amount of NBO in the glass network present favorable ion exchange conditions, important for the formation of silanol (Si–OH) groups, the subsequent condensation of the SiO 2 layer and the formation HCAp on their surface [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All samples were dried at 75 • C for 2 days and calcinated in different temperatures (Table 1). The synthesis of silica-based mesoporous nanocarriers (100% mol SiO 2 ) (mSbN), was performed through a modified sol-gel method, as described before [13]. The cetyltrimethylammonium bromide (CTAB) was used as the agent for the mesoporous structure.…”
Section: Synthesis Of Silica Based Nanoparticles (Sbns)mentioning
confidence: 99%